Analytical solutions of reaction-diffusion-convection type equations from porous media by the Laplace-Adomian method - WELLOT, Yanick Alain Servais; Nkaya, Gires Dimitri (International Journal of Applied Mathematical Research, 2022)
The aim of this paper is to solve analytically fluid flow problems in a porous medium, the Laplace-Adomian method gives algorhims that converge faster to achieve the exact solution when it exists.